Growing up in the age of uncertainty. Some anthropological comments on the case of Lombardy - Angela Biscaldi (EtnoAntropologia)
This paper will focus on the cultural representations of the present economic crisis in young people living in Lombardy. It is based on the data gathered through 700 questionnaires administered to high-school senior students in that region during school year 2013/2014, as well as on 75 in-depth interviews with young people aged 18-31 living in Milan. Using those data concerning, on the one hand, young people considering whether to continue their study and, on the other hand, young people who completed their formal education and are now facing up to a challenging labour market, this paper puts forward some observations on “growing up in times of uncertainty”, i.e. on how the new generations represent their own future and their responsibility in making change possible.